2010
DOI: 10.1016/j.febslet.2010.04.046
|View full text |Cite
|
Sign up to set email alerts
|

The uremic solute indoxyl sulfate acts as an antioxidant against superoxide anion radicals under normal‐physiological conditions

Abstract: a b s t r a c tThe effect of the uremic solute indoxyl sulfate (IS) on scavenging superoxide anion radicals (O ÅÀ 2 ) generated from both the xanthine/xanthine oxidase (X/XO) system and activated neutrophils was investigated by electron paramagnetic resonance spectroscopy, combined with 2-ethoxycarbonyl-2-methyl-3,4-dihydro-2H-pyrrole-1-oxide (EMPO). The findings show that the presence of normalphysiological serum concentrations of IS (0.1-10 lM) resulted in decreased formation of EMPOsuperoxide adduct without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…Several studies reported a positive linear correlation between IS and oxidative biomarker levels, acrolein and 8-hydroxyl-2′-deoxyguanosine, which accelerate progression of uraemia [Nakagawa et al 2006;Fujii et al 2009]. However, one needs to mention that recent literature suggests antioxidant activity of IS against hydroxyl radicals under physiological conditions [Miyamoto et al 2010].…”
Section: Molecular Mechanisms Of Action Of Ast-120mentioning
confidence: 99%
“…Several studies reported a positive linear correlation between IS and oxidative biomarker levels, acrolein and 8-hydroxyl-2′-deoxyguanosine, which accelerate progression of uraemia [Nakagawa et al 2006;Fujii et al 2009]. However, one needs to mention that recent literature suggests antioxidant activity of IS against hydroxyl radicals under physiological conditions [Miyamoto et al 2010].…”
Section: Molecular Mechanisms Of Action Of Ast-120mentioning
confidence: 99%
“…The activity of XO was determined by monitoring the conversion of X to uric acid, according to a previous report. 17) ALP was used to confirm the positive reaction. EPR Spectroscopy Superoxide concentrations from human neutrophils were determined using EPR spin trapping with EMPO, and the scavenging activity was calculated from the relative peak intensities corresponding to the EMPO-superoxide adduct (EMPO-OOH) EPR signal.…”
Section: Methodsmentioning
confidence: 99%
“…7) but epigallocatechin acted as a superoxide anion generator under the conditions used by Sato et al [21]. Indoxyl sulfate has been shown to be an endogenous antioxidant with superoxide anion scavenging activity generated from activated neutrophils and also it has been shown to eliminate hydroxyl radicals [22]. Catecholamines have also been shown to have a direct effect on scavenging superoxide anion radicals [23].…”
Section: Orac Mr5 Of Pure Phytochemicalsmentioning
confidence: 99%